Working with coaches and their teams in youth and collegiate sport in the USA: A Commentary - Bloom, G. A.; Lefebvre, J. S. (International Journal of Sports Science & Coaching, 2018)
Sport psychology literature contains many accounts of mental training consultants working with teams from youth sport to the highest levels of amateur and professional sports. Recently, Simon Jenkins interviewed Andy Gillham about his career as a full-time coaching consultant at the youth and collegiate levels. We found the article quite illuminating, and we enjoyed being privy to the ins and outs of this unique and innovative career. This commentary will focus on information contained in Jenkins` interview, emphasizing Gillham`s professional journey, his implementation of evidencebased coaching, and the importance of resiliency.